2003
DOI: 10.1002/icd.307
|View full text |Cite
|
Sign up to set email alerts
|

Poverty, stress, and support: patterns of parenting behaviour among lower income black and lower income white mothers

Abstract: The relation between parenting behaviour and poverty has been established, with impoverished parents' related experiences of stress and support typically implicated in the development of negative parenting behaviour. Additionally, differences in parenting behaviour have been identified for families with different ethnic backgrounds. However, whether ethnicity continues to effect similar differences in families' parenting behaviour in the face of the challenges associated with poverty or whether poverty leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 13 publications
3
23
1
1
Order By: Relevance
“…These findings suggest that foster mothers engage in parenting in the context of a larger community in which immediate and extended family, and their church play an important role in supporting their parenting endeavors, whereas biological mothers appear to be engaged in parenting in a mostly solitary context with occasional support from immediate family. The differences obtained between the maternal groups on community support is consistent with previous research (Soliday et al, 1994;Middlemiss, 2003); however, the current study differs from these previous findings in that the previous literature focused on one maternal group (i.e., foster mothers or biological mothers), whereas the current study focused on both and was able to directly compare differences in perceptions of social support.…”
Section: Journal Of Familysupporting
confidence: 87%
See 1 more Smart Citation
“…These findings suggest that foster mothers engage in parenting in the context of a larger community in which immediate and extended family, and their church play an important role in supporting their parenting endeavors, whereas biological mothers appear to be engaged in parenting in a mostly solitary context with occasional support from immediate family. The differences obtained between the maternal groups on community support is consistent with previous research (Soliday et al, 1994;Middlemiss, 2003); however, the current study differs from these previous findings in that the previous literature focused on one maternal group (i.e., foster mothers or biological mothers), whereas the current study focused on both and was able to directly compare differences in perceptions of social support.…”
Section: Journal Of Familysupporting
confidence: 87%
“…In addition, the authors found that foster mothers reported the importance of community support, particularly church related support, in maintaining parenting satisfaction and decreasing parenting stress. This finding of the importance of community support is in contrast to findings in non-foster mother samples that indicate that these mothers perceived low-levels of support from the community for their parenting (Middlemiss, 2003). A qualitative study on foster parent perceptions of factors influencing successful parenting (Buehler, Cox, & Cuddeback, 2003) sheds additional light on the stressors and supports that impact parenting practices of foster parents.…”
mentioning
confidence: 55%
“…More specifically, difficult or tenuous parentchild relationships among low SES youth are often linked to parental stress, distress, and depression (Prelow, Weaver, Bowman, & Swenson, 2010;Wadsworth, Raviv, Santiago, & Etter, 2011). Relational problems also arise from parents' perceived isolation and lack of support (Middlemiss, 2003;Raikes & Thompson, 2005). One study (McLeod & Owens, 2004), for example, explored several dimensions of youth well-being among low SES families, using the National Longitudinal Surveys of Youth.…”
mentioning
confidence: 97%
“…Whereas general life stresses can include relational and economic factors, parenting stress is relevant only as it relates to the parenting role (e.g., caregiver's thoughts or feelings about her relationship with her child, perception of parenting as negatively affecting social life or partnerships, perception of efficacy in the family caregiver role; Baker, Perilla, & Norris, 2001). Parenting stress, which is influenced by social class, number of children, and relationship satisfaction (Elder, Eccles, Ardelt, & Lord, 1995;Middlemiss, 2003), has been linked to poor parenting practices, child abuse and neglect, poor psychological health (Larson, 2004), and child emotional and behavioral problems (Owen, Thompson, & Kaslow, 2006). Some findings suggest that involvement in an IPV relationship results in higher levels of parenting stress and negatively affects the parenting relationship, while others do not (Holden & Ritchie, 1991;Levendosky & Graham-Bermann, 1998).…”
mentioning
confidence: 99%